Novel insights into an old methodology: upgrading the use of tethered swimming - Morouco, P. G. (ISBS Proceedings Archive (Michigan), 2017)
More than 40 years ago, Magel (1970) used tracings with a compensating polar planimeter to measure propelling forces in swimming. By that time, average height of the curves was calculated in millimetres and converted to average force measures. Advances in technology, permitted picking up old methodologies and give them new features. In fact, the use of a force transducer to assess the forces exerted by a swimmer in his/her real environment turned out to be a useful methodology for training prescription. Nowadays, a load-cell can continuously record the force-time curves and to straightaway provide the calculation of several variables. Thus, swimmers can perform a tethered test with immediate feedback, enhancing the effects for performance improvement. This paper aims to identify and describe procedures that fits the purpose of biomechanical evaluation, i.e., to provide the necessary tools for training prescription, rapidly after the evaluations.